A Synthesizable Thyristor-Like Leakage-Based True Random Number Generator - Kim, Seohyun; Kim, Jang Hyun; Lee, Jongmin (Proceedings -Design, Automation and Test in Europe, DATE, 2025)
As the demand for random data in cryptographic systems continues to rise, the importance of True Random Number Generators (TRNGs) becomes increasingly crucial for securing cryptographic applications. However, designing a TRNG that is reliable, secure, and cost-effective presents a significant challenge in hardware security. In this paper, we propose a synthesizable TRNG design based on a thyristor-like leakage-based (TL) structure, optimized for secure applications with small area and cost-efficiency. Our design has been validated using a 65-nm CMOS process, achieving a throughput of 0.397-Mbps within a compact area of 14.4-μm2, offering considerable cost savings while maintaining high randomness and area-throughput trade-off of 27.57 Gbps/mm2. Moreover, this TRNG can be synthesized as a standard cell through a semi-custom design flow, significantly reducing design costs and enabling design automation, which streamlines the process and reduces the time and effort required compared to traditional full-custom TRNGs. Additionally, as it is library characterized, the number of TL TRNG cells can be freely adjusted to meet specific application requirements, offering flexibility in both performance and scalability. To assess its randomness, the NIST statistical test suite was applied, and the proposed TL TRNG successfully passed all applicable tests, demonstrating its randomness.
Keywords: Cost effective; Cryptographic applications; Cryptographic systems; Leakage-based; Low-costs; Random data; Random number generators; Synthesizable; True random number generator; True randoms; Hardware security; Leakage-based; Low-cost; Synthesizable; TRNG